Analyzing Voltage Stability in IEEE 57-Bus System Using Voltage Collapse Proximity Index (VCPI) - Samburi, Nurfaraliyana; Nor, Ahmad Fateh Mohamad; Salimin, Suriana; Zaini, Nur Ellysa Mu’izz Mohd (Journal of Electronic Voltage and Application, 2025)
The comprehensive study highlights how power systems have evolved over the decades to meet the growing demand for electricity. Increasing energy consumption has made maintaining voltage stability a significant challenge. As a result, voltage stability has become a critical parameter that requires in-depth analysis in modern power systems. This research aims to improve voltage stability analysis in the IEEE 57-bus system using VCPI analysis to identify the weakest buses, enhancing the accuracy of stability assessments and reducing the risk of voltage instability. The proposed methodology utilizes MATLAB software to conduct the power flow analysis, followed by the Voltage Collapse Proximity Index (VCPI) analysis to pinpoint the weakest bus in the 57-bus network. Bus 18 was observed to have the highest VCPI value of 1.0359 pu, signifying it as the weakest bus in the network. It is recommended to apply voltage stability techniques like VCPI for a more comprehensive analysis. Instead of relying on initial values such as voltage magnitude, VCPI provides a reliable measure for assessing the risk of voltage instability, offering valuable insights for future research.